Merchants' adoption of mobile payment in emerging economies: the case of unorganised retailers in India. Issue 1 (2nd January 2022) - Mishra, Vishal; Walsh, Isabelle; Srivastava, Ankur
ABSTRACT: A substantial body of literature shows that in addition to increased convenience, mobile payments may result in greater efficiency and contribute to digital and financial inclusion. Although researchers have paid a lot of attention to individual adoption of mobile payment, few studies investigate mobile adoption by businesses, especially unorganised businesses in developing countries. To address this research gap, we use an exploratory grounded theory approach to examine unorganised retailers in urban India. Using 56 semi-structured interviews with merchants, we highlight an emerging mobile payment ecosystem that includes technology value, regulatory bodies, non-regulatory bodies, and merchant dispositions. The data highlight power asymmetry in this ecosystem and show that time-varying interactions among its components determine merchants' behaviour and resulting (non-) adoption. We find that not only are Indian regulatory bodies the most powerful influencers in the diffusion of this technology; they are also important market actors. This study provides insights into the process of technology adoption by unorganised businesses in India. Moreover, this study sheds light on the important link unorganised retailers create between businesses and bottom-of-the-pyramid consumers, as well as between the state and its marginalised citizens, thereby confirming that such retailers are indispensable partners in economic growth and technology-driven inclusion.